Efficiency of capital formation of utility enterprises: the case of Ukraine - Korbutiak, Alina; Slobodyanik, Yu; Bagatska, K (Instituto Federal de Educação, Ciência e Tecnologia de São Paulo, 2021)
The paper aims to analyze the approaches to capital formation of Ukrainian utility enterprises, identify their impact on the financial results of entities and formulate recommendations to ensure the efficiency of utility enterprises. The methodological basis of the study is comparative analysis, theoretical studies, statistical information, analytical data prepared by governmental and non-governmental bodies, the best practices. In the course of the research were collected and processed empirical data of 30 utility enterprises from 11 regions of Ukraine with different economic, demographic, climatic and administrative conditions. The conducted research confirms that the capital invested in the municipal enterprises does not increase their efficiency. Funding from a municipal budget without disclosure of the criteria for providing such resources does not enlarge the profitability of utility enterprises and often used to cover their losses, which lead to capital disruption. In order to increase the efficiency of utility enterprises and the fair distribution of municipal budget funds it was proposed to introduce the disclosure of additional information about capital formation; to strengthen the managers’ responsibility for the quality of publishing information with the introduction of special KPIs; and to conduct financial and performance audit, including in terms of capital formation.
Independent Journal of Management & Production